Induction of tyrosine aminotransferase in mice is inhibited by activated metabolites of ortho- aminoazotoluene - V. I. Kaledin; S. I. Ilnitskaya; N. A. Popova; O. A. Koval; I. A. Pyshnaya; L. F. Gulyaeva (Вавиловский журнал генетики и селекции)
Aminoazo dyes and other hepatocarcinogenic substances inhibit glucocorticoid-mediated induction of adaptive enzymes, including tyrosine aminotransferase (TAT), in mouse and rat liver. There is a specific relationship between the effect of a carcinogen on TAT induction and its liver carcinogenicity in animals. Presuming tumor development being initiated not directly by the chemicals employed but their metabolically activated derivatives, the question arises whether TAT induction is inhibited by carcinogen metabolites or by their parent compounds. The goal of this paper is to shed some light on the issue. Mouse strains differing in the sensitivity to both carcinogenic and antiglucocorticoid (TAT induction inhibitory) effects of the mouse-specific carcinogen ortho- aminoazotoluene (OAT) underwent a set of experimental procedures: ablation of gonadal and adrenal glands, administration of inhibitors (CoCl2, pentachlorophenol), inducers (3,4- benzopyrene, Aroclor 1254, 20-methylcholanthrene) of xenobiotic-metabolizing enzyme activities, and others. The results unequivocally confirm that glucocorticoid induction of TAT activity in mouse liver is inhibited by activated metabolite(s) of OAT rather than by its intact molecules. In contrast, nonspecific genotoxic agents such as cyclophosphamide and cisplatin exert no effect on TAT induction by glucocorticoids. The wide occurrence (practically in each TAT-expressing  hepatocyte) and rapidly reversible inhibition of enzyme induction by the carcinogen point to the epigenetic nature of this phenomenon.